2022
DOI: 10.3390/curroncol29110644
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Radiation Therapy as Salvage in the Treatment of Relapsed Primary CNS Lymphoma

Abstract: Primary central nervous system lymphoma (PCNSL) is a rare malignancy. Standard of care is upfront high-dose methotrexate (HD-MTX) chemotherapy, while cranial radiation is more commonly used in the salvage setting. In this retrospective study, we aimed to investigate the safety and efficacy of salvage cranial radiation in PCNSL. PCNSL patients who received upfront HD-MTX chemotherapy and salvage cranial radiation after treatment failure between 1995 and 2018 were selected. Radiological response to cranial radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Our analysis showed that in the second line of the treatment, 5 patients received therapy according to the Study-G-PCNS-SG-1 protocol, 3 patients were treated with RTOG 93-10, and one patient was treated with combination of HD-MTX/AraC. Previously published studies showed that treating relapse of PCNSL with higher dose of radiotherapy (≥30Gy) are linked to the higher CR rates ( 12 ). New modalities of treatment are being developed for patients with PCNSL relapse.…”
Section: Discussionmentioning
confidence: 81%
“…Our analysis showed that in the second line of the treatment, 5 patients received therapy according to the Study-G-PCNS-SG-1 protocol, 3 patients were treated with RTOG 93-10, and one patient was treated with combination of HD-MTX/AraC. Previously published studies showed that treating relapse of PCNSL with higher dose of radiotherapy (≥30Gy) are linked to the higher CR rates ( 12 ). New modalities of treatment are being developed for patients with PCNSL relapse.…”
Section: Discussionmentioning
confidence: 81%